Reform redux: measurement, determinants and reversals - Nauro F. Campos; Roman Horváth (Institute for the Study of Labor (IZA), 2006)
We construct objective measures of privatization, internal and external liberalization reform efforts, across countries over time, and investigate their determinants, reversals and macroeconomic impacts. We find that GDP growth determines external liberalization and privatization, concentration of political power drives internal liberalization, and democracy underpins all three. We find that FDI inflows reduce the probability of privatization reversals, labour strikes increase that of internal liberalization reversals, and OECD growth increase that of external liberalization reversals. We replicate previous studies and find that the macroeconomic effects of reform (when measured objectively) tend to be larger and more precisely estimated.
Keywords: E23; D72; H26; O17; 330; reform : liberalization; privatization; political economy; transition; Systemtransformation; Politische Reform; Deregulierung; Kapitalmarktliberalisierung; Direktinvestition; Transformationsstaaten